Effect of SiC particle size on hardness and wear behavior of TIG melted hard surface layer AISI Duplex-2205 Steel - Paijan, Lailatul Harina; -, Suryanto; Maleque, Malaysia (2019)
AISI Duplex-2205 steel with hard surface layer provides a protection against wear during any sliding motion. SiC particle size with average sizes of 20 µm, 60 µm and 100 µm were used as surface preplacement to AISI Duplex-2205 surface in this investigation. The aim is to evaluate the influence of different SiC particle size melted at heat input of 768 J/mm on hardness and wear behavior. The surface characterization, hardness and wear behavior were conducted using scanning electron microscopy, Vickers micro-hardness and reciprocating wear tester respectively. Characterization of the TIG melted layer reveals the existence of new phases containing a dendritic structure. The surface hardness developed was higher than the substrate hardness due to the dendrite microstructure. The SiC particle size of 100 µm produced lower friction value of 0.37 and wear rate of 2.3 x 10-6 mm3/Nm compared to 3.2 x 10-6 mm3/Nm for 20 µm particle size. The improvement of wear properties is directly related to the higher hardness value of TIG melted hard surface layer AISI Duplex-2205 steel.